Law for the Rationalization and Sustainability of the Local Government, Abolition of the Local Competence regarding Education and its Consequences for the UNED (Spanish National University of Distance Education) Affiliated Centers - Fernández-Miranda, Jorge (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2015)
The current piece of work has the purpose to study the consequences of the 27 December 27/2013 Law for the Rationalization and Sustainability of the Local Government, complying with the loss of competence regarding education and its consequences on the services offered by the UNED (Spanish National University of Distance Education) affiliated centers. In this vein, we need to consider the meaning and extent of the temporary regime passed by the ruler, the new demands established for committees, the consideration of the competence case of study as a delegated competence as well as the terms, deadline and content in which the delegation should take place.